Size‐Resolved Dry Deposition Velocities of Dust Particles: In Situ Measurements and Parameterizations Testing. Issue 19 (2nd October 2018) - Bergametti, G.; Marticorena, B.; Rajot, J. L.; Foret, G.; Alfaro, S. C.; Laurent, B.
Abstract: Bulk and size‐resolved particle concentrations were measured at 2.1 and 6.5 m above the soil surface during an intense dust deposition event that occurred in June 2006 in Niger. Bulk concentration measurements were performed using two tapered element oscillating microbalance instruments, and the size‐resolved particle concentrations (from 0.3 to 20 μm) using two optical particle counters. The deposition fluxes derived from the bulk concentrations and those derived from the size‐resolved ones are in very good agreement. The largest deposition fluxes are recorded when the dust concentrations are maximal. The temporal evolution of the dust deposition flux follows that of the dust concentration. This is not the case of the dry deposition velocities that are most of the time controlled by the wind friction velocity. The results also show that large particles are strongly sensible to rebound when the wind friction velocity is the highest. Size‐resolved dry deposition velocities are compared with the rare measurements of dust deposition velocities over bare sandy soils and are confronted to existing parameterizations of the dry deposition velocity. The parameterization of Zhang and Shao (2014, https://doi.org/10.5194/acp‐14‐12429‐2014 ) appears to be the only one able to reproduce satisfyingly the measured dry deposition velocities on sandy soils in the 1‐ to 10‐μm particle size range. Indeed, unlike others, this scheme considers the desert sandy surfaces as rough surfaces, allowing the interception of dust particles by the sand grains and/or by the small roughness elements present on the surface. Key Points: A dust deposition event allows the determination of dust deposition fluxes and dry deposition velocities using the flux gradient method The time evolution of dry deposition velocities is mainly controlled by the wind friction velocity and, for large particles, by rebound Measured dry deposition velocities are in better agreement with parameterizations that consider bare sandy surfaces as rough surfaces